Association of important malting traits in barley (Hordeum vulgare) - SARKAR, B; VERMA, R P S; MISHRA, B (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2003–05 to study genetic variability, genotypic and phenotypic correlation coefficients for 13 malting quality traits in a set of 131 barley (Hordeum vulgare L) genotypes grown at 2 locations. Significant genetic variability was observed for all the 13 characters studied. Significant location effects for most of the quality traits were observed. There were significant genotypic and phenotypic correlation co-efficients between 60 pairs of characters, 35 with positive and 25 with negative associations. Hot water extract, the most important malt quality trait showed significant correlation data with grain (hectolitre weight, 1 000 g weight, bold grain) and malt (friability and homogeneity) quality traits